Bootstrapping Conceptual Normativity?. (9th December 2020) - Thornton, Tim
Abstract: Both anti‐reductionist and reductionist accounts of meaning face challenges accounting for first acquiring linguistic concepts. This paper examines whether Ginsborg's 'primitive normativity' might explain such learning. Primitive normativity can be understood as either a 'no conception' or a 'local conception' version. Rejecting the 'no conception' account in favour of a 'local conception' of a rule or norm expressed in context‐dependent demonstrations provides one response to Fodor's argument that concept learning is impossible. It also provides anti‐reductionism with at least one stepping stone to learning full‐blown linguistically articulated concepts based on a more primitive local form of normativity.